Foaming ability and stability of silica nanoparticle-based triple-phase foam for oil fire extinguishing: experimental. Issue 4 (2nd October 2018) - Zhou, Rifeng; Dou, Xiaoxiao; Lang, Xuqing; He, Limin; Liu, Jianlin; Mu, Shanjun
ABSTRACT: The triple-phase foam has been widely used in oil fire extinguishing, and its two key parameters for application are the foaming ability and stability. We present a comprehensive study on the foam expansion ratio (FER) and drainage time, where factors such as the foam morphology, zeta potential of particles, foam mixing homogeneity, surfactant concentration, particle mass percentage, and specific surface area of the particle are investigated in detail. The dependence relationship curves of FER and drainage time with respect to the latter four variables are given through experiments, and optimal parameter values are selected. Moreover, the scaling laws correlating these variables are in agreement with the experimental results, and some necessary parameters are obtained by data fitting. These analyses are beneficial to better understand the foaming ability and stability mechanism of the triple-phase foam and to prepare materials of high performances for oil fire extinguishing.